Northern textiles. A - Varma, J. R. (SAGE business cases., 2020)
Cases of the Indian Institute of Management, Ahmedabad are prepared as a basis for class discussion. They are not designed to present illustrations of either correct or incorrect handling of administrative problems.© 2020 by Indian Institute of Management, Ahmedabad.